Efforts to Improve Short Surah Memorization Skills in Early Childhood through Project Based Learning Model - Lubna, Lubna; Ramdhan, Dadan F. (Al-Aulad: Journal of Islamic Primary Education, 2023)
The study aimed to enhance short surah memorization skills in early childhood through the Project Based Learning (PBL) model. Classroom Action Research was employed as the research method. Findings demonstrate that the PBL model effectively improves the memorization abilities of short surahs in early childhood. This improvement was evident from the initial assessment before intervention and continued throughout the cycles, with a notable increase in cycle II. Implementation involved steps such as listening to recitations, displaying and reading colorful verse segments, repetition by children, group arrangement of verses, and presentations. Analysis revealed significant development in memorization skills from 6.25% in cycle I to 62.25% in cycle II, indicating the efficacy of the PBL method in supporting memory retention and enhancing short surah memorization among young children.